2020
DOI: 10.3390/biomedicines8080263
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Supplementation Concurrent with Nutrition Education Accelerates the Wound Healing Process in Patients with Diabetic Foot Ulcers

Abstract: Trials on nutritional supplements for the treatment of diabetic foot ulcer (DFU) have only evaluated the effects of supplementation with specific nutrients. Additionally, nutrition education has not been a systematic part of these studies. The aim of this study was to evaluate the effects of a nutrient-dense formula combined with nutrition education on wound healing in DFU patients. Twenty-nine patients were randomly assigned to the treatment group (n = 15) receiving two servings of supplements daily plus nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…These facilitate access to people with diabetes and are an educational tool that can improve HbA1c levels [ 45 ]. Health education provides many benefits to patients [ 46 ]. Nonetheless, it is true that it requires a responsibility on the part of the patients [ 47 ] and that a standardization and simplification of the different applications is necessary, since there is a decrease in communication with health professionals [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These facilitate access to people with diabetes and are an educational tool that can improve HbA1c levels [ 45 ]. Health education provides many benefits to patients [ 46 ]. Nonetheless, it is true that it requires a responsibility on the part of the patients [ 47 ] and that a standardization and simplification of the different applications is necessary, since there is a decrease in communication with health professionals [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that glycaemic control was suboptimal for patients diagnosed with T2D, and the highest uncontrolled glycaemic rate was 50.0% (95% CI in Gaza City. The lowest was 32.3% (95% CI [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] in Khan Younis. It is reasonable that Gaza City is considered an urbanized City compared to the rest of the Gaza Strip regions, while Khan Younis is a Palestinian refugee camp [49].…”
Section: Discussionmentioning
confidence: 99%
“…It may have a negative impact on the quality of life and diabetes self-management [ 25 ]. Thus, the diabetic patient should have special management of his/her nutrition, including added sugar, which has a critical role in the wound-healing process [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to examine if these nutrients can shift diabetic wounds from chronic/non-healing to normal wounds by improving inflammation status. It has been reported that DFU patients have a significantly low intake of the aforementioned nutrients [29,30]. However, evidence of the benefit to wound healing in DFUs through management of inflammation is lacking for a combination of these essential nutrients.…”
Section: Introductionmentioning
confidence: 99%